Wettability of Graphene Coated on Aluminum Substrate with Microstructure Modification - Dou, Yu-Hao; Bai, Qingshun; Guo, Wanmin; Guo, Yongbo; Du, Yunlong (Current Nanoscience, 2023)
Background: As a new type of coating material, graphene has an important application prospect in creating hydrophobicity on the material surface. It can be seen that research on the wettability of graphene has a very actual significance in its application. Graphene membrane can change the wettability of the aluminum surface effectively. It can be combined with the traditional method to tune the wettability of the metal surface. Adding the microstructure is a very common method for changing the wettability. Therefore, the results have guided significance for the practical application of graphene in controlling the wettability of aluminum substrate with microstructure. Methods: This paper uses molecular dynamics to simulate graphene’s adsorption and wetting behavior on the aluminum substrate with microstructure and to calculate energy changes in the two processes. Results: The adsorption state of graphene is related to the aspect ratio of the microstructure. When the aspect ratios of the microstructure become larger, the graphene can be completely absorbed by the substrate, causing larger binding free energy and higher adhesion spontaneity of graphene. The wetting contact angles of the substrate with graphene are significantly higher than those of the aluminum substrate without graphene. Conclusion: The aspect ratio can influence the free energy and the binding energy, causing different states in graphene. The large aspect ratio will increase the absolute value of the free energy and release more binding energy, causing a more stable state. The graphene may prevent the deformation of the hydrogen bond and cause worse wettability. The results have been of great significance for the practical application of graphene in controlling the wettability of aluminum substrate with microstructure.
Keywords: adsorption mechanism